Chimeric antigen receptor T-cells targeting IL-1RAP: a promising new cellular immunotherapy to treat acute myeloid leukemia. Issue 7 (8th July 2022) - Trad, Rim; Warda, Walid; Alcazer, Vincent; Neto da Rocha, Mathieu; Berceanu, Ana; Nicod, Clémentine; Haderbache, Rafik; Roussel, Xavier; Desbrosses, Yohan; Daguindau, Etienne; Renosi, Florain; Roumier, Christophe; et al.
Abstract : Background: Acute myeloid leukemia (AML) remains a very difficult disease to cure due to the persistence of leukemic stem cells (LSCs), which are resistant to different lines of chemotherapy and are the basis of refractory/relapsed (R/R) disease in 80% of patients with AML not receiving allogeneic transplantation. Methods: In this study, we showed that the interleukin-1 receptor accessory protein (IL-1RAP) protein is overexpressed on the cell surface of LSCs in all subtypes of AML and confirmed it as an interesting and promising target in AML compared with the most common potential AML targets, since it is not expressed by the normal hematopoietic stem cell. After establishing the proof of concept for the efficacy of chimeric antigen receptor (CAR) T-cells targeting IL-1RAP in chronic myeloid leukemia, we hypothesized that third-generation IL-1RAP CAR T-cells could eliminate AML LSCs, where the medical need is not covered. Results: We first demonstrated that IL-1RAP CAR T-cells can be produced from AML T-cells at the time of diagnosis and at relapse. In vitro and in vivo, we showed the effectiveness of IL-1RAP CAR T-cells against AML cell lines expressing different levels of IL-1RAP and the cytotoxicity of autologous IL-1RAP CAR T-cells against primary cells from patients with AML at diagnosis or at relapse. In patient-derived relapsed AML xenograft models, we confirmed that IL-1RAP CAR T-cells are able to circulate in peripheral blood and to migrate in the bone marrow and spleen, are cytotoxic against primary AML cells and increased overall survival. Conclusion: In conclusion, our preclinical results suggest that IL-1RAP CAR T-based adoptive therapy could be a promising strategy in AML treatment and it warrants the clinical investigation of this CAR T-cell therapy.